Supporting the UN SDGs transition: Methodology for sustainability assessment and current worldwide ranking - Lorenza Campagnolo; Fabio Eboli; Luca Farnia; Carlo Carraro (Kiel Institute for the World Economy (IfW), 2017)
The FEEM project APPS - Assessment, Projections and Policy of Sustainable Development Goals lies in the stream of research related to the quantitative assessment of the 17 Sustainable Development Goals (SDGs), adopted by the United Nations at the end of September 2015. The project consists of two phases. The first, retrospective, derives a composite multi-dimensional index and a worldwide ranking of current sustainability. This allows informing on strengths and weaknesses of today socioeconomic development, as well as environmental criticalities, all around the world. The second phase, prospective, aims evaluating the future trends of sustainability in the world by 2030. The assessment is carried out by means of an extended version of the recursivedynamic computable general equilibrium ICES macro-economic model that includes social and environmental indicators. The final goal is to highlight future challenges left unsolved in next 15 years of socio-economic development and analyze costs and benefits of specific policies to support the achievement of proposed targets. The methodology goes through the following steps: screening of indicators eligible to address the UN SDGs; data collection from relevant sources; organization in the three pillars of sustainability (economy, society, and environment); normalization to a common metrics; aggregation of the 25 indicators in composite indices by pillars as well as in the multi-dimensional index. The final ranking includes 139 countries. North European countries are at top of the ranking (Sweden, Norway and Switzerland).
Keywords: O44; O57; Q01; 330; Sustainable Development Goals; Composite Index; ranking; indicators